Factors Associated to Recurrent Wheezing in Infants Under One Year of Age in the Province of Salamanca, Spain: Is Intervention Possible? a Predictive Model - Mallol-Villablanca, E (Elsevier Doyma, 2016)
Objectives: Wheezing is a very common problem in infants in the first months of life. The objective of this study is to identify risk factors that may be acted upon in order to modify the evolution of recurrent wheezing in the first months of life, and to develop a model based on certain factors associated to recurrent wheezing in nursing infants capable of predicting the probability of developing recurrent wheezing in the first year of life. Methods: The sample was drawn from a cross-sectional, multicentre, descriptive epidemiological study based on the general population. A total of 1164 children were studied, corresponding to a questionnaire response rate of 71%. The questionnaire of the Estudio Internacional de Sibilancias en Lactantes (EISL) was used. Multiple logistic regression analysis was used to estimate the probability of developing recurrent wheezing and to quantify the contribution of each individual variable in the presence of the rest. Results: Infants presenting eczema and attending nursery school, with a mother who has asthma, smoked during the third trimester of pregnancy, and did not consume a Mediterranean diet during pregnancy were found to have a probability of 79.7% of developing recurrent wheezing in the first year of life. In contrast, infants with none of these factors were seen to have a probability of only 4.1% of developing recurrent wheezing in the first year of life. These results in turn varied according to modifications in the risk or protective factors. Conclusions: The mathematical model estimated the probability of developing recurrent wheezing in infants under one year of age in the province of Salamanca (Spain), according to the risk or protective factors associated to recurrent wheezing to which the infants are or have been exposed. © 2015 SEICAP